Managing digital enterprise : ten essential topics - Xu, Jun (Atlantis Press Imprint: Atlantis Press, 2014)
This book describes the setup of digital enterprises and how to manage them, focusing primarily on the important knowledge and essential understanding of digital enterprise management required by managers and decision makers in organizations. It covers ten essential knowledge areas of this field: • Foundation of Digital Enterprise • Technology Foundation and Talent Management for Digital Enterprise • Digital Enterprise Strategy Planning and Implementation • B2C Digital Enterprise: E-tailing • B2C Digital Enterprise: E-Services • B2B Digital Enterprise and Supply Chain • Digital Platforms • Digital Marketing and Advertising • Digital Payment Systems • Mobile Enterprise Overall, this text provides the reader with the basics to understand the rapid development of digitization, facilitated by the dramatic advancements in digital technologies, extensively connected networks, and wider adoption of computing devices (especially mobile devices), as more and more organizations are realizing the strategic importance of digitization (e.g., sustainable growth of the organization, competitive advantage development and enhancement) and are embarking on digital enterprise.